Openness and equilibrium determinacy under interest rate rules - Fiorella De Fiore; Zheng Liu (European Central Bank (ECB), 2002)
This paper shows that the conditions under which inflation-targeting interest rate rules lead to equilibrium uniqueness in a small open economy in general differ from those in a closed economy. As the monetary authority adjusts nominal interest rates in response to inflation, the real interest rate changes. The overall effect of this change on aggregate demand has important implications for equilibrium determinacy. In an open economy, an increase in the real interest rate is transmitted to aggregate demand through an intertemporal substitution effect, as in a closed economy, but also through a terms of trade effect that is absent in the closed economy. These effects move aggregate demand in opposite directions. We find that, in a broad class of models, the conditions for local equilibrium uniqueness depend crucially on the degree of openness to international trade. Openness matters not only quantitatively, but also qualitatively.
Keywords: E52; E58; F41; 330; indeterminacy; interest rate rules; small open economy; Terms of Trade